Effects of Mesoscopic Structure on Crack Resistance of Asphalt Mastic and Calibration of Contact Parameters. Issue 3 (April 2021) - Zheng, Chuanfeng; Teng, Guocui; Chen, Xiangyin; Li, Xuan
Abstract: This paper investigated the effects of mesoscopic structure on crack resistance of asphalt mastic basing on the bending failure simulation with discrete element method. A Dynamic Link Library wrote by C++ is proposed for the modelling process of particle filling. Response surface and variance analysis are used to calibrate mesoscopic mechanical parameters of contact model, determine the influence of different parameters on deformation in bending failure test and the relationship between the parameters is fitted by mathematical formula. The effects of air void content and fine aggregate surface texture on crack resistance of asphalt mastic at -10 °C were studied then. It was proved that the adhesive strength and bonding area between fine aggregates co-influence the ultimate bending failure load, and the contact stiffness influences the ultimate bending deflection. Mathematical correlation formula between the radius of binding area and the critical stress that satisfies the ultimate load of asphalt mastic beam can be fitted in same form. The flexural strain energy density of asphalt mastic is increased with the decrease of air void content. The results are of positive significance for improving the mechanical properties of asphalt road in cold regions.